Neurocognition and brain structure in pediatric patients with type 1 diabetes - Kaufmann, Liane; Pixner, Silvia; Starke, Marc; Zotter, Sibylle; Köhle, Julia; Meraner, Dagmar; Kremser, Christian; Egger, Karl; Schocke, Michael; Hofer, Sabine (Journal of Pediatric Neuroradiology, 2012)
Recent findings suggest that in addition to severe hypoglycemia, chronic hyperglycemia may also hamper the cognitive development of patients with type 1 diabetes. Executive and memory dysfunctions mediated by frontoparietal and temporal brain structures are frequently reported to be associated with type 1 diabetes. However, most studies investigating pediatric patients with diabetes focus on either brain function or brain structure.The current study combines neuropsychological and structural brain imaging methods (i.e., voxel-based-morphometry) to study the neurofunctional integrity of frontoparietal brain areas. We investigated 30 children with type 1 diabetes and 19 healthy controls. Children with diabetes were divided into two groups representing better (HbA1c ≤ 7.9%) and worse (HbA1c ≥ 8.0%) glycemic control. Our findings were threefold: First, results revealed significant group differences with respect to neuropsychological performance (i.e. response accuracies on a marker task tapping frontoparietal brain functions). Second, structural imaging disclosed significant group differences between patients and controls regarding gray matter volume in frontal (anterior cingulate) and occipital (cuneus, bordering precuneus) brain regions and regarding white matter in middle temporal and occipital gyri as well as in the ventromedial temporal lobe (uncus). Third, disease duration, age at diagnosis and white matter volume in a hippocampal region-of-interest (but not HbA1c levels, intelligence, total gray/white matter or other white/gray matter regions-of-interest) explained 56% of neuropsychological performance variance. Taken together, our findings are among the first to provide evidence of a direct link between brain function and brain structure in pediatric patients with type 1 diabetes.
Keywords: Type 1 diabetes; neuropsychological performance; HbA1c; voxel-based-morphometry; gray matter; white matter; metabolic control; neurocognition; pediatrics